Association of Lymphopenia with Short Term Outcomes of Sepsis Patients; a Brief Report - Sheikh Motahar Vahedi, Hojat; Bagheri, Aida; Jahanshir, Amirhosein; Seyedhosseini, Javad; Vahidi, Elnaz (Archives of Academic Emergency Medicine, 2019)
Introduction: Studies have claimed that low lymphocyte count is independently correlated with 28-day survival of sepsis patients. Therefore, this study aimed to evaluate the value of lymphopenia in predicting the short-term outcome of sepsis patients. Methods: This cross-sectional study was performed on sepsis patients referred to the emergency department during an 8-month period and relationship of lymphopenia with 28-day mortality and probability of septic shock and readmission due to sepsis was assessed. Results: 124 cases with the mean age of 66.12 Â± 15.82 (21-90) years were studied (54.8% male). 81 (65.3%) cases had lymphopenia (59.3% male). Lymphopenic patients had a significantly higher mean age (p = 0.003), higher need for ICU admission (p < 0.001), higher prevalence of 28-day septic shock (p < 0.001), higher 28-day mortality (p < 0.001), higher probability of readmission due to sepsis (p = 0.048), and higher SOFA score (p < 0.001). During 28 days of follow up, 57 (46%) patients were expired. They had a higher prevalence of septic shock (p < 0.001) and higher SOFA score (p < 0.001). Multivariate analysis showed that septic shock (OR=364.6; 95% CI: 26.3 to 5051.7; p = 0.001) and lymphopenia (OR=19.2; 95% CI: 1.7 to 211.3; p = 0.016) were the independent predictors of 28-day mortality. Conclusions: Based on the findings, lymphopenia was independently associated with higher 28-day mortality and lymphopenic patients were older than the control group and had a significantly higher need for ICU admission, higher probability of 28-day septic shock and readmission due to sepsis, and higher SOFA score.